2020
DOI: 10.1111/jocn.15470
|View full text |Cite
|
Sign up to set email alerts
|

Describing objectively measured intensive care nurses’ physical work activity behavioural patterns during a 12‐hr shift

Abstract: Aim and objectives: To describe intensive care unit (ICU) nurses' physical work activity behavioural patterns over 12 hr using dual accelerometry, following a job demands-recovery framework. Background: Limited studies utilised accelerometry to objectively analyse nurses' physical workloads. Little is known about intensive care nurses' physical activity patterns during a 12-hr shift.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 30 publications
2
24
0
Order By: Relevance
“…, 2020a). Moreover, we found different patterns of physical activity behaviours across the sample during a 12-h shift (Yu et al. , 2020b).…”
Section: Introductionmentioning
confidence: 98%
See 4 more Smart Citations
“…, 2020a). Moreover, we found different patterns of physical activity behaviours across the sample during a 12-h shift (Yu et al. , 2020b).…”
Section: Introductionmentioning
confidence: 98%
“…Evidence indicates that nurses' occupational physical activity involves prolonged standing and walking, excessive physical job demands and long work hours (Chappel et al, 2017;de Campos et al, 2018;Fiedler et al, 2012). Prior research found that high levels of standing and dynamic standing were involved in ICU nursing during a 12h shift (Yu et al, 2020b). Moreover, studies identified that nurses' physical activity during work hours was more energy-intensive compared to their physical activity during leisure time (Daud et al, 2019;Lee et al, 2005;McCarthy et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations